Aging, sexual intimacy, and challenges in contemporary India: A qualitative study - Srivastava, Sanchita; Upadhaya, Puja (Frontiers in Psychology, 2022)
An Individual’s life is shaped by age norms practised in a particular society. In most societies, there is a deadline for every life event. Sexual intimacy is an essential part of every individual. However, sexual intimacy seems for young individuals and middle-aged and older to be considered asexual. Those who share sexual intimacy at a later age have to face the consequences for this age-inappropriate behaviour in society. This paper analyses 'Badhaai Ho' film to explore the consequences of sharing sexual intimacy by middle-aged heterosexual couples in their fifties as it is forbidden by prevalent social norms. This study also explores the role of the family in dealing with the repercussions of actions against the prescribed social norms. Thematic analysis suggests that society has predefined age bound box for individuals with different age categories. The middle-aged couple suffered various consequences for breaking the prescribed age bound box. The role of the family is found to be crucial in mending the box by replacing it with an updated version. There are also gender differences in attitude towards sexual intimacy. Implications of this study can be utilised to explore the pathway of social change in existing social (age) norms in any society.